Area control of road traffic proceedings of the symposium organized by the Institution of Civil Engineers ... [et al.] at the Institution of Civil Engineers, London, February 1967. (Institution of Civil Engineers, 1967)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium with ICE, IMechE and IEE held in February 1967.